2022
DOI: 10.1007/s00415-022-11009-x
|View full text |Cite|
|
Sign up to set email alerts
|

Management of hepatitis B virus prophylaxis in patients treated with disease-modifying therapies for multiple sclerosis: a multicentric Italian retrospective study

Abstract: Background Patients with multiple sclerosis (MS) often receive disease-modifying therapies (DMTs) that can expose them to reactivation of potential occult hepatitis B virus (HBV) infection (pOBI). We aimed to evaluate the MS Centers behavior regarding HBV screening and prophylaxis in a large cohort of MS patients receiving anti-CD20 or cladribine. Methods Retrospective, multicentric study recruiting Italian MS patients treated with rituximab, ocrelizumab a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Our results are especially relevant in view of the low rate of screening for HBVr in patients with MS undergoing rituximab-containing regimens. A recently published multicentre study including 53 anti-HBc-positive subjects showed that 21 received antiviral prophylaxis, and only 13 had HBV DNA monitoring during therapy for assessment of HBVr [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are especially relevant in view of the low rate of screening for HBVr in patients with MS undergoing rituximab-containing regimens. A recently published multicentre study including 53 anti-HBc-positive subjects showed that 21 received antiviral prophylaxis, and only 13 had HBV DNA monitoring during therapy for assessment of HBVr [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…HBV reactivation has been found in patients undergoing corticosteroid therapy in a number of studies 16,18,19 . In addition, there are studies in the literature investigating the risk of HBV reactivation in many different diseases that cause immunosuppression 20–23 . However, as far as we know there has been no research on HBV reactivation in CS, an immunosuppressive disease, and only case reports have been published.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,19 In addition, there are studies in the literature investigating the risk of HBV reactivation in many different diseases that cause immunosuppression. [20][21][22][23] However, as far as we know there has been no research on HBV reactivation in CS, an immunosuppressive disease, and only case reports have been published. Since CS is an uncommon condition and HBV infection is not routinely screened for in the community, the frequency of HBV infection among this patient population is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, B cells have been linked to MS and its progression as well as T cells [ 8 ], and the second-generation anti-CD20 recombinant humanized monoclonal antibody (mAb) ocrelizumab has been approved for the treatment of both relapsing–remitting MS (RRMS) and primary progressing MS (PPMS) [ 7 , 9 , 10 , 11 ]. It selectively induces B cell depletion, resulting in an immunosuppressive effect [ 12 , 13 , 14 , 15 ]. Although ocrelizumab efficiently depletes B cells in blood, some B cells and CD20 negative plasma cells persist in lymphatic organs and the inflamed central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, despite its remarkable efficacy, ocrelizumab is associated with an increased risk of infection and reactivation [ 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Considering the intense B cell depletion induced by ocrelizumab, the aim of this study was to investigate the alterations in B cell activation markers prior to and during ocrelizumab treatment and their relationship with the occurrence of infectious events.…”
Section: Introductionmentioning
confidence: 99%